0797 Restless Legs Syndrome and Perceived Olfactory and Taste Dysfunction: A Community-Based Study. (27th May 2020) - Zhuang, S; Yuan, X; Ma, C; Yang, N; Liu, C; Na, M; Winkelman, J W; Wu, S; Gao, X
Abstract: Introduction: Restless legs syndrome (RLS), an under-recognized sensorimotor condition worldwide, is thought to be a prodromal symptom of Parkinson's disease as suggested by previous evidences. However, its association with prodromal chemosensory impairments, including olfactory or taste dysfunction, has remained largely unknown. Few studies of small sample sizes were conducted in predominantly Caucasian populations and results were inconsistent. Methods: We performed a cross-sectional analysis including 90, 337 Chinese adults free of neurodegenerative diseases in the Kailuan study in 2016. Presence of RLS was defined using revised RLS diagnostic criteria and further verified by Cambridge-Hopkins questionnaire for RLS. Perceived olfactory and taste dysfunction was collected via a questionnaire. The association between RLS and perceived olfactory and taste dysfunction was assessed using logistic regression model, adjusting for potential cofounders such as age, sex, smoking, alcohol consumption sleep conditions and medical history. Results: RLS was associated with high odds of having perceived olfactory and/or taste dysfunction (adjusted odds ratio =5.92; 95% confidence interval, 3.11, 11.3). The significant association persisted when using Cambridge-Hopkins questionnaire for RLS (adjusted odds ratio =5.55; 95% confidence interval, 2.37-13.0) or when excluding participants with major chronic diseases. Conclusion: RLS was associated with increased odds of perceived olfactory and taste dysfunction. Support: This research was supported by start-up grant from the College of Health and Human Development and the Department of Nutritional Sciences, Pennsylvania State University, the Institute for CyberScience Seed Grant Program, Pennsylvania State University, and Natural Science Foundation of Hebei Province (H2018209318).